Quelle place au travail des agriculteurs dans la fabrication d’une agriculture durable ? - Pascal Béguin; Valérie Pueyo (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper is focused on work in the making of a sustainable agriculture. We emphasize three types of issue. The first one is related to the objectification of occupational health. Agriculture is a tough sector, which produces exclusion and which is far from attractive. The second is related to design. Farming today is not sustainable, and technical systems need to be designed. But the changes need to be actionable at work. So we present three ways needed in order to think out the workers’ activity during the design process. The third issue is related to Policy: sustainable development is also a future to bring together. We suggest that this collective dimension could be grasped as a « project », which takes into consideration the projects of farmers in order to define the aims of sustainable agriculture.